Motivasi Beramal dalam Perspektif Al-Quran dan Hadist: Studi Literatur - Turrohma, Mitra; Alwis, Dona Ana Yori; Satriadi, Inong (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the concept of charitable motivation based on the Quran and hadith. This article uses a qualitative approach with the reivew literature method, which is a study conducted by analyzing various relevant sources including articles, books, and other documents. Research data collection is carried out through scientific articles published through Google Scholar. The articles used are articles published in the 2015–2024-time interval. Data analysis is carried out qualitatively by assuming data reduction, data presentation, and conclusion drawing. Hasl data analysis shows that doing good deeds is not only in the form of material, but we can also do charity using what we have such as science or helping others who have both energy and mind, in doing charity must be based on sincere intentions and only hope for pleasure from Allah alone. A sincere person will not get any losses. In fact, sincerity can provide peace of mind, so that the heart is airy and peaceful. It is because his heart is only focused on one goal, which is the pleasure of Allah. The Qur'an and Hadith are the two main sources that motivate Muslims to do charity. The benefits of charity can not only be felt when we are in the world but also in the hereafter. The charity that we can do also varies from charity to others or charity to Allah SWT such as worshiping and avoiding all His prohibitions